Production of Learning Materials Using Computer Assisted Instruction Technology : Case Study on the Topic of the Road History - Sopha, Peerapat; Kumphong, Jetsada; Amornpinyo, Prach; Jantarakot, Sirinapa; Bubpi, Attaphol; Phonkasi , Suban (Journal of Graduate MCU KhonKaen Campus, 2024)
The objectives of this article are to produce learning materials using the Computer Assisted Instruction (CAI) in the teaching of road history and to inspect the quality of the instructional tool. The Index of Item Objective Congruence (IOC) and the Content Validity Index (CVI) were investigated. The evaluation of the quality of the Computer Assisted Instruction was performed by 3 experts on two aspects. Firstly, the content and presentation, and the material technique and design-it was shown that the evaluated items are in accordance with the objectives of the Computer Assisted Instruction, with IOC higher than 0.5 and thus passing the criteria. Secondly, the aspect of Content Validity Index (CVI) was evaluated and showed the Item-level CVI (I-CVI) higher than 0.8, which also passed the accepted criteria. The Scale-level CVI (S-CVI) was over 0.8, also passing the accepted criteria. In conclusion, the Computer Assisted Instruction (CAI) for teaching road history possesses the quality and can be used in classroom to assist the Active Learning method and the 21st Century instruction.